2019
DOI: 10.1186/s12894-019-0457-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and risk factors of patients with upper urinary tract urothelial carcinoma and postoperative recurrence of bladder cancer in central China

Abstract: Background To investigate the prognostic risk factors and postoperative recurrence of bladder cancer in patients with upper urinary tract urothelial carcinomas (UTUCs). Methods Data of 439 UTUC patients were retrospectively analyzed. Follow-up and analysis of smoking effects, consumption of traditional Chinese medicine containing aristolochic acid, history of bladder cancer, age, sex, presence or absence of diabetes mellitus (DM), metformin use, tumor characteristics (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 35 publications
0
33
1
Order By: Relevance
“…For example, patients with unifocal, < 2 cm, and low-grade lesions without local invasion are considered to have low-risk disease[ 9 ]. In the case of low-grade/low-stage TCC of the renal pelvis, open surgery is being replaced by endoscopic surgery[ 10 , 11 ]. However, ureteroscopic tumor ablation remains associated with a high risk of disease recurrence and progression due to inadequate assessment of risk stratification by imaging or tumor biopsy[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with unifocal, < 2 cm, and low-grade lesions without local invasion are considered to have low-risk disease[ 9 ]. In the case of low-grade/low-stage TCC of the renal pelvis, open surgery is being replaced by endoscopic surgery[ 10 , 11 ]. However, ureteroscopic tumor ablation remains associated with a high risk of disease recurrence and progression due to inadequate assessment of risk stratification by imaging or tumor biopsy[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30% of patients with UTUC will have bladder recurrence (BR) [27,28]. Series of studies have been done on the prognosis and risk factors of bladder recurrence after surgery [28,29]. Our previous study found lower tumor grade, tumor multifocality, concomitant carcinoma in situ, and tumors located in the lower ureter were significant risk factors of bladder recurrence after RNU [27].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that UTUC spans two neighboring localities has led to the comparison of RPTs and UTs. The incidence of RPTs seem to be higher 3 , 6 , 7 than that of UTs and RPTs often present a more advanced disease stage at the time of diagnosis 6 , 7 . Conversely, UTs are more likely to be organ-confined and have a greater association with bladder tumor history or recurrence 5 , 7 .…”
Section: Introductionmentioning
confidence: 91%